Effects of ionic liquid pretreatment on pyrolysis characteristics of a high-sulfur bituminous coal. (15th December 2019) - Liang, Peng; Qin, Xizhuang; Bai, Guangming; Wu, Zexing; Sun, Dekui; Zhang, Yaqing; Jiao, Tiantian
Highlights: ILs exhibited higher extraction yield than optimized organic solvent pyridine. [Bmim]Cl showed selective extraction ability for sulfur-containing compounds. More sulfur was released during pyrolysis process through IL pretreatment. High carbon number components in tar decreased after IL pretreatment. IL pretreatment could improve the product distribution and increase oil yield. Abstract: Four different ionic liquids (ILs) were used to identify their extraction properties on high-sulfur bituminous coal. And the effect of ILs pretreatment on pyrolysis characteristic was investigated in a fixed-bed reactor. The imidazolium-based ILs used namely: 1-butyl-3-methyl-imidazolium chloride ([Bmim]Cl), 1-butyl-3-methyl-imidazolium bromide ([Bmim]Br), 1-butyl-3-methylimidazolium hydrogen sulfate ([Bmim]HSO4 ), 1-butyl-3-methyl-imidazolium tetrafluoroborate ([Bmim]BF4 ). All the selected ILs exhibited extraordinary extraction ability for oxygen-containing compounds, mainly furans and ethers. Among them, [Bmim]Cl got the highest extraction yields of 20.82% and performed selective extraction ability for sulfur-containing compounds with a relative content of 5.10% in light oils. Compared with pyridine pretreated coal (R-PY), the yields of CO and CO2 in pyrolysis gas showed increase trend when coal pretreated by ILs (R-ILs). The relative contents of tricyclic and larger PAHs, sulfur-containing compounds, and oxygen-containing compounds in tar from pyrolysis of [Bmim]Cl and [Bmim] Br treated coal increased significantly than R-PY tar, while phenols got decreased. High carbon number components from R-ILs tar reduced dramatically compared with R-PY tar, which was conducive to the upgrading of tar, after pretreated with ILs, the sulfur content was reduced. The crosslinks between coal macromolecules structure were destroyed after pretreated by ILs, and the pyrolysis products distribution had evident change. The oil phase yield got a substantial increase while [Bmim]Cl obtained highest oil yield of 24.89%.